Theoretical Calculations For Sputtering Yield of Iron Bombarding by (H, D, T, He) Ions - Jawad, Enas A .; Jassim, Mustafa K.; Tawfeek, Huda M . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Extended calculations for sputtering yield through bombed Iron – target by ( H,D ,T ,He ) ions plasma are accomplished .The calculations include changing the input parameters : the energy of ( H,D ,T ,He ) ions plasma, the hit target angle of Iron, change atomic mass of incident ion. The program TRIM is used to accomplish these calculations. The results show that sputtering yield is directly dependent on these parameters. It can change the incident angle of ( H,D ,T ,He ) ions and energy lead to a significant change in sputtering yield on the other hand. The sputtering yields are highly affected by changing of incident ion mass at fixed other target parameters. It can be shown from calculation that whenever increased incident ion mass increase sputtering yield, increases with incident ions energy and then begins to decline, sputtering will not occur , at incident ion energies below the threshold energy . In this study we found that the sputtering yield depends on incidence angle, incident ions energy and atomic mass of target.